Coalitions, alignements et alliances interétatiques (Note) - Lemieux, Vincent; Traoré, Namatié; Bolduc, Nathalie (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1994)
Coalition theory has developed outside the field of international relations in the wake of game theory, in laboratory experiments, and in the study of government coalitions. Four parameters can be used to predict the formation and development of coalitions : the benefits sought by the players, the resources at their disposal, the non-utilitarian linkages between them, and the decision threshold to be reached. In the field of international relations, many studies have dealt with coalitions, alignments, and interstate alliances. They can be grouped into three schools of thought. First, there is the economic school where States are seen as seeking to maximize the benefits they gain from working together. Second, there is the power relationship school, with States forging alliances mainly for self-protection from external military threats. Finally, there is the structural school, less developed than the two other ones, which is based on the affinities, rivalries, or neutralities between States. The effects of alliances, in particular military ones, have been much debated. Some authors claim they are a factor for stability in the international System ; others claim the opposite. The research note concludes by suggesting there is a need to develop a truly political theory of alliances, one that could integrate theories more economic or sociological in nature.